577 Engineered non-pathogenic synthetic biotic producing L-arginine synergize with PD-1-based cancer immunotherapy. (9th November 2020) - Canale, Fernando; Basso, Camilla; Li, Ning; Sokolovska, Anna; Perotti, Michela; James, Michael; Jin, Wenjie; Theurillat, Jean-Philippe; Leventhal, Daniel; West, Kip; Lora, Jose; Sallusto, Federica; et al.
Abstract : Background: The availability of L-arginine in tumors is a key determinant of an efficient anti-tumor T cell response. Consequently, the elevation of typically low L-arginine levels within the tumor may greatly potentiate the anti-tumor responses of immune check point inhibitors, such as PD-L1 blocking antibodies. However, currently no means are available to locally increase intra-tumoral L-arginine levels. Methods: We used a synthetic biology approach to develop an engineered probiotic Escherichia coli Nissle 1917 strain that colonizes tumors and continuously converts ammonia, a metabolic waste product that accumulates in tumors, into L-arginine. Results: Colonization of tumors with these bacteria elevated intra-tumoral L-arginine concentrations, increased the amount of tumor-infiltrating T cells, and had striking synergistic effects with PD-L1 blocking antibodies in the clearance of tumors. The anti-tumor effect of the living therapeutic was mediated by L-arginine and was dependent on T cells. Conclusions: These results show that engineered microbial therapies enable metabolic modulation of the tumor microenvironment leading to enhanced efficacy of immunotherapies.